PPPs Policy Entity Network Change and Policy Learning in Mainland China - Ying Jiang; Qian Wang (Complexity)
Since 1995, Public-Private Partnerships (PPPs) mode has been applied in mainland China accompanied by the issuance of a series of PPPs policies. Taking 201 policy documents promulgated from 1995 till 2019 as a research sample, this paper explores PPPs policy entity network change and policy learning behind it in China. Research results show the following: (1) China’s PPPs policy entity network has mainly gone through three stages: partial-focus network with bad stability, loose-multiactor network with general stability, and balanced-multiactor network with good stability; (2) the key players are NPC in the first stage, MOF and NDRC in the second stage, and MOF and 8 other government entities in the third stage; (3) policy learning behind PPPs policy entity network change is government learning in the first stage and lesson-drawing in the second and third stages.